Evaluation of nonverbal communication skills in autistic children - chikhi, mabrouk; boutghane, mohamed el taher (Journal of Social Sciences and Humanities, 2020)
Autism,as any other developmental disorder, affects a child’s both natural growth and nervous system. It also affects the different areas of growth in his/her life such as communication, social interaction, behaviour and his/her readiness to learning and training. Autism takes different forms as in delayed or loss of linguistic development, anger or crying outbursts, laughter for no reason, absence of risk perception, playing in an odd way, along with a difficulty in self-care. It is one of the most widespread, interesting and researched disorders among scholars and specialists. The importance of the study is in its focus on the autistic children. It aims at evaluating and analysing forms of weakness in their non-verbal communication, also known as ‘social interaction skills’. The latter is considered as among the most important features of communication which represent a clear symptom in an autistic child. This can be attained through the use ofLina Seddic ’s ‘Assessment of non-verbal communication among autistic children’. It is a five-dimension measurement scale which represents forms of nonverbal communication (Common Attention, Visual Interaction, Imitation, Listening and Understanding, as well as Using Reference to what is Desirable). To attain the objective of the study, a group of ten (10) cases which are diagnosed with autism disorder, no associated disability, aged between 4 and 6 years has been chosen. After going through the study procedures, the following results have been obtained: There is a clear deficiency in the non-verbal communication skills amongst the study group who suffer from autism disorder especially in common attention, visual interaction, imitation, listening and understanding, as well as using reference to what is desirable On the basis of these results, some recommendations and suggestions have been provided to researchers and scholars interested in Autism.The most important of which are; focusing on developing the linguistic and communicative aspects and essentiallynon-verbal social communication skills which this category suffers from. Considering that non-verbal communication precedes verbal communication and is an essential stage leading to it. In addition, the former is associated with different aspects such as the sensory and cognitive aspects